Understanding the interaction between teacher and students in senior high school classroom - Saputri, Ririn Vijayanti Indah; Kus Indratno, Toni Kus; Kusfiana, Rani (International Journal on Education Insight, 2023)
Education plays a central role in the formation of individuals and society. The relationship between teachers and students in the educational environment is a key factor that influences students' learning experiences and development. Teachers, as learning agents, have the responsibility to create an environment that supports students' academic and social growth. This research focuses on teacher-student interactions related to Academy Reaction and Social Reaction in class X students at SMA Muhammadiyah 4 Yogyakarta. In the context of lessons, including physics subjects, there has been no research that specifically examines teacher-student interaction relationships in the aspects of Academy Reaction and Social Reaction at SMA Muhammadiyah 4 Yogyakarta. This research aims to fill this knowledge gap and identify factors that influence students at these schools. This research provides valuable insight into the role of teachers in students' academic and Social Reactions and emphasizes the need to consider variations in teaching approaches to meet students' diverse needs.